Copper doped titanium dioxide (TiO2) nanoparticles for enhanced photocatalytic activity under visible light irradiation - Leong, Sheng Yau (2013)
Titanium dioxide (TiO2) is best known for its inexpensiveness and highly available as a photocatalyst. However, due to its wide-bandgap of 3.2 eV and the fast recombination of electron-hole pair, they have contributed to the inability to use the sunlight sufficiently as well as hindering for any reaction to happen. The objectives of the title are to synthesize a copper (Cu) doped TiO2, to inspect the photocatalytic activity of the synthesized TiO2 and to study the kinetic of the degradation of methylene blue (MB). A Cu salt is first synthesized using copper nitrate (Cu(NO3)) mixed in the glycerol phase. The preparation of TiO2 was carried out by the sol-gel method and the resulted Cu salt is added into it to in a 10 wt.% Cu/TiO2 manner. The resulted gel was aged for a day before it was heated up in the oven for 24 hours, which resulted in powder form. It was grinded and calcinated at 300 oC for an hour. The photocatalytic activity of the synthesized catalyst was inspected with the degradation of methylene blue (MB). As a result, the photocatalytic activity had been increased and the K0 ((k0H/K0)+ k0 is 0.03236 mg L-1 min-1 while K0 is 9.32615 X 10-3 4L mg-1.